Chemotherapy dosing in achondroplastic dwarfism: a case report and review of literature. (6th October 2016) - Elsoueidi, R.; Gresham, C.; Michael, L.; Chaney, D.; Mourad, H.
Summary: What is known and objective: case description: A 74‐year‐old female with achondroplastic dwarfism was diagnosed with ER‐, BR‐ and HER2‐ breast cancer. No guideline currently exists to direct chemotherapy dosing in this population. She received neoadjuvant chemotherapy based on body surface area utilizing actual height and weight with dose‐dense doxorubicin and cyclophosphamide followed by paclitaxel with the use of granulocyte colony‐stimulating factor. Satisfactory clinical response and remission were achieved, and treatment proceeded without any significant toxicity or delays. What is new and conclusion: In the absence of guideline recommendations, dosing chemotherapy based on actual height and weight in patients with achondroplastic dwarfism may be safe and appropriate. Abstract : In the absence of guideline recommendations, dosing chemotherapy based on actual height and weight in patients with achondroplastic dwarfism may be safe and appropriate.